Limiting Directors' Liability - Deborah A. DeMott (Washington University Law Quarterly, 1988)
Over half the states now expressly permit the inclusion of provisions that limit or eliminate directors' liability for money damages in corporations' articles or certificates of incorporation, under circumstances specified by a statutory enabling provision. Many states modeled their enabling provisions closely on the Delaware statute, with some variations. Other state statutes instead define a limited set of circumstances under which a director's misfeasance or nonfeasance will make the director liable. A few states permit subject corporations to opt out of the statutory restrictions on liability." In contrast, the Virginia statute imposes a cap on monetary damages for which directors and officers could be liable as a result of certain actions. The following sections of this article review the technical and policy issues raised by these statutes and by recent changes in statutes regulating indemnification and D & O insurance. In general it is noteworthy that substantial questions arise as to the interpretation and efficacy of many of these statutes. Relatedly, many of these statutes reflect little effort by their drafters to integrate their import with other sections of the statute that appear pertinent to issues of directors' liability. As a result of these unfortunate deficiencies, the risk exposure of directors and officers to liability is unpredictable. If in fact the goal of these statutory revisions is to enhance the insurability of directors' litigation risks by reducing directors' liability, the uncertain effect of some of these statutes could undercut enhanced insurability. In addition some of these provisions are drafted in a highly detailed style that, perversely enough, makes it difficult to determine precisely the situations to which they do and do not apply. Extreme particularization of this sort runs counter to the conventional wisdom that general corporation statutes should be drafted consistently with a preference for general as opposed to narrow applicability and for prescribing broad standards that apply to more rather than fewer types of transactions. Finally, the clear impetus for enacting the provisions was the perceived crisis in the availability of D & O insurance for directors of public companies. Many statutes, however, apply much more broadly, permitting the reduction of directors' liability in all corporations, including closely-held ones, and, in some states, in relationship to claims that raise issues of the defendant's loyalty to the corporation.
Keywords: Liability insurance; Executives